Development and nutritional evaluation of a tempeh and sweet potato leaf-based functional beverage for adolescent nutrition - Nur Khoiriyah; Rizaluddin Akbar; Muhammad Zakaria (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Adolescent anemia remains a nutritional problem in Indonesia. Anemia affects 16.2% of the population in the country. Tempeh and sweet potato leaves are rich in iron, protein, and antioxidants, making them beneficial for adolescent nutrition. Few studies have combined these two ingredients in beverages. This study aimed to develop a beverage product using tempeh and sweet potato leaves to support adolescent nutrition. This study was conducted from August to October 2025 using a completely randomized design with three replications. The proportions of tempeh to sweet potato leaves were 100:0 (F0, control), 90:10 (F1), 80:20 (F2), 70:30 (F3), and 60:40 (F4). The product formulation was conducted at the Nutrition Laboratory of the Universitas Muhammadiyah Cirebon. The analysis included sensory evaluation (30 semi-trained panelists), proximate, iron, and antioxidant content, formulation selection, and nutritional contribution to the needs of adolescents. Data were analyzed using ANOVA and Duncan’s test. Significant differences were observed in color, aroma, taste, texture, overall preference, moisture, ash, fat, protein, iron, and antioxidant activity among the formulations (p<0.05). Meanwhile, carbohydrate content did not differ significantly (p=0.184). F1 was selected, yielding 3.43% protein, 4.84 mg/100 g iron, and 17494.73 ppm antioxidant activity (IC50). In conclusion, F1 is recommended as the best formulation to support adolescent nutrition.